Aktivitas Antioksidan Dan Kandungan Β-Karoten Dodol Labu Kuning Dengan Penambahan Bunga Kecombrang Sebagai Pengawet Alami - Lestari, Dwi, Dra. Titik Suryani, M.Sc (2015)
Dodol is a traditional food that is quite popular in Indonesia. The alternative materials are pumpkin and flowers kecombrang. This study aims to determine the antioxidant activity, the content of β-carotene, organoleptic quality and public acceptance. This study used an experimental method with a completely randomized design (CRD) two factors: factor 1 were composition of glutinous rice flour and pumpkin : 50%+50% (L1), 40% + 60% (L2), 30%+70% (L3) and factor 2 were flowers kecombrang : 15% (K1), 25% (K2), 35% (K3). The results showed that there is influence of glutinous rice flour and pumpkin and kecombrang flowers on the antioxidant activity and beta-carotene content. The highest antioxidant activity in the treatment dodol L1K1(glutinous rice flour 50% + pumpkin 50% + kecombrang flowers 15%) was 33.84% and the highest contents of beta-carotene in the treatment L2K2 (glutinous rice flour 40% + pumpkin 60% + kecombrang flowers 25%) was 0,0035μg / g, while the antioxidant activity and the lowest contents of beta-carotene was 11.81% and 0,0013μg / g in the treatment L3K3(glutinous rice flour 30% + pumpkin 70% + kecombrang flowers 35%). Dodol pumpkin all treatments were less preferred by the panelists.